Australian English: Its Evolution and Current State - Collins, Peter (International Journal of Language, Translation and Intercultural Communication, 2012)
This paper provides a critical overview of research on Australian English (‘AusE’), and of the vexing questions that the research has grappled with. These include: What is the historical explanation for the homogeneity of the Australian accent? Was it formed by the fi rst generation of native-born Australians in the ‘Sydney mixing bowl’, its spread subsequently facilitated by high population mobility? Or is the answer to be found in sociolinguistic reconstructions of the early colony suggesting that a uniform London English was transplanted to Australia in 1788 and that speakers of other dialects quickly adapted to it? How is Australia’s national identity embodied in its lexicon, and to what extent is it currently under the infl uence of external pressure from American English? What are the most distinctive structural features of AusE phonology, morphosyntax and discourse? To what extent do allegedly unique Australian features such as sentence-final but and yeah-no in discourse serve the social role of indexing ‘Australianness’? What is the nature and extent of variation – regional, social and ethnic – in contemporary AusE? Are such regional phonological differences as /æ/ /a/ variation increasing or diminishing? Does there exist a pan-ethnic variety of AusE that is particularly associated with younger Australians of second generation Middle Eastern and Mediterranean background? Has contemporary AusE consolidated its own norms as an independent national standard?